(untitled) (KULT_online, 2014)
What does landscape mean in the middle of the 18th century? Following this question Thomas Forrer analyses discursive moments and figures in early modern texts from natural history, art theory, and philosophy. In the Baroque period nature would show the impermanence of all mundane life, and in the modern age the alienation of nature would be the current topic. To Forrer, nature appears differently in the era of enlightenment from 1720 to 1770. The experience of nature would be perceived as the origin of human potency. Landscape as spectacle would be then the projection surface for every thinkable meaning, the ’putting-before-one’s-eyes’ supplies the possibility of thinking further and becoming potent in the first place. In respect thereof, Forrer observes his sources with a focus on ’natural history’, ’art and aesthetics’, and ’poetry’.